ROMANIAN EDUCATIONAL SYSTEM AND MULTICULTURALISM. CHALLENGES IMPLIED BY THE NATIONAL LAW IN EDUCATION: FROM ENSURING MINORITIES' RIGHTS TO SEGREGATION DANGER - ION ALBULESCU (Studia Universitatis Babes-Bolyai, 2011)
ABSTRACT. All educational programs that are based on the idea of multiculturalism must found on the principle of eliminating discrimination and of eliminating the dichotomy between the culture belonging to majority and the culture belonging to minority, as well as on a lot of approaches developed for preserving and valorizing specificity. The National Low in Education from Romania comprises a series of regulations regarding the way schools function, these schools being organized on ethnical criteria, thus, education language within these schools being the language of the respective minority. These regulations can lead, aspect underlined by this research, to segregation and isolation.